Is the quest for efficiency harmful to health equity? An examination of the health efficiency-equity nexus in OECD countries over the past two decades - Bousmah, Marwân-al-Qays; Abu-Zaineh, Mohammad; Combes, Simon; Ventelou, Bruno (Social science & medicine (1982), 2025)
Has the quest for efficiency in OECD health systems impacted the social gradient of health? We examined the cross-dynamics of the health system equity-efficiency nexus among OECD countries in the past two decades. We used a three-step methodology based on annual macro-level data from 36 OECD countries for the period 2004–2021. First, we estimated the efficiency of health systems using a stochastic frontier analysis. We then assessed the equity of health systems using simple measures of income-related inequality in self-assessed health. Lastly, we estimated the dynamic relationship between health system efficiency and equity using a panel Granger causality analysis. We also stratified the analysis by type of health system: viz. publicly- vs. privately-dominated health service provision. We find evidence for a bidirectional causality between health system efficiency and equity. An increase in health system efficiency leads to an increase in socioeconomic inequalities in health; a result particularly salient in countries with predominantly private health service provision. Interestingly, decreases in socio-economic inequalities in health are likely to lead to higher health system efficiency, especially in countries where the health system relies predominantly on public provision. The pursuit of efficiency gains in OECD health systems has not been a precondition for socioeconomic equity in health. Adverse effects of efficiency-seeking interventions on health equity are particularly apparent in the private provision of healthcare. However, addressing health inequalities provides a plausible route to enhance efficiency. •There is a long-standing debate on the equity-efficiency nexus within health systems.•We analyse the bidirectional efficiency-equity relationship in OECD health systems.•Efficiency gains jeopardize equity, especially when health service provision is mainly private.•However, reducing health inequality may lead to higher health system efficiency.